Development of deaf students addressing difficulties in the teaching process learning chemistry: The challenges of inclusion (Research, Society and Development, 2021)
Inclusive education has advanced in the Brazilian educational scenario and several measures have been taken, such as officializing LIBRAS as the second language of Brazil and the mother tongue of deaf people and opening enrollments of deaf students in regular schools, and these measures were crucial for the advancement of the intellectual and cognitive development of these individuals, however, over time some challenges have also arisen to be faced during the teaching - learning process, especially by teachers. With regard to teaching chemistry to deaf students, this challenge is greater due to the complexity of the theme. This work analyzes the advances that have occurred in Brazil, promoting inclusive education and the main challenges faced by chemistry teachers during the inclusion process. Thus, a theoretical approach was made, in which a search was carried out, in general, without any time limit, in order to obtain the largest number of published works on the topic discussed.